PENGARUH CYBERBULLYING BODY SHAMING PADA MEDIA SOSIAL INSTAGRAM TERHADAP KEPERCAYAAN DIRI WANITA KARIR DI PEKANBARU - Dela Geofani; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The rapid development of social networking brings a new trend to carry out acts of oppression online or better known as cyberbullying. Cyberbullying is a reproachful behavior, giving negative judgment through social media Instagram. The phenomenon that arises at this time is the emergence of body shaming actions. Body shaming is the act of commenting on one's physical, appearance, or self-image which is an act of bullying. The purpose of this study was to determine whether there is an influence of cyberbullying body shaming on Instagram social media on the confidence of career women in Pekanbaru. The theory used is stimulus-response (S-R).The method used in this study is a quantitative method with an explanatory format. In the analysis of quantitative research methods using inferential statistical analysis. Researchers collected data using a questionnaire distributed via links to 100 respondents and the technique of determining samples using simple random sampling techniques. To determine how much influence these two variables have, the researcher uses simple linear regression analysis. Processing of questionnaire test data using SPSS version 16. The results of this study indicate that the influence of cyberbullying body shaming on social media Instagram on the confidence of career women in Pekanbaru, the regression coefficient values obtained in this study were Y = 10.204 + 0.741X with a significance level of 0.000 less than α = 0.05, so it can be concluded that the variable X affects the Y variable. The coefficient of determination (r2) obtained is 0,5752and (Rsquare) is 0.331 results from the squaring of the correlation coefficient 0.575 x 0.575 This means that there is a cyberbullying body shaming effect on self confidence of 33.1% with a low category, career women have entered at a good level in commenting and using Instagram social media, the remaining 66.9% is influenced by other variables outside of this study. Keywords :Cyberbullying, Body Shaming, Confidence